Factors Affecting University Selection During Pandemic : a Study on Indonesian High School Students - Rocky Nagoya; Innocentius Bernarto; Ferdi Antonio (ADI Publisher, 2020)
The purpose of this study is to find an important factor for high school students in selecting university. It is vital for university to have a significant amount of new students enrolled to ensure a strong financial capability for them. This research focuses on quality, reputation, spirituality value, economic and emotional value factors in relation with intention to enroll in university. The respondents are year 11 and 12 high school students from DKI and Banten Province. The sampling technique is convenience sampling due to a pandemic situation. Smart PLS is used to analyze the data. This study found that quality, spirituality value, reputation and emotional value has positive correlation on intention to enroll, whereas quality and economic have no positive correlation toward intention to enroll.